Peranan Anggaran Biaya Produksi Sebagai Alat Pengendalian Dalam Kaitannya Dengan Realisasi Biaya Produksi Pada PT. Sigma Utama - Hasibuan, David (Jurnal Ilmiah Kesatuan (JIK), 2010)
There are ways or methods to reach the goal of a company, one of them is by establishing cost budget. Cost control has a close correlation with work planning measured in money unit. Budget is a plan organized and comprehensive, stated in monetary unit to operate and as resources of a company during a certain period in the next time. The purpose of this research is to find out the role of production budget based on orders in the company that carry out production process based on job orders. In addition, this research conducted to know whether budget arrangement and its implementation in the company have been appropriate and accurate to support the management in increasing production cost efficiency. This research has been done by the author at PT Sigma Utama located in Jalan Raya Cibinong, West Java. PT Sigma Utama is a paint maker company. The result of this research shows that an accurate production cost budget will support the management in increasing cost control, so that the budget will not deviate in its realization.